2017
DOI: 10.1016/j.jval.2016.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Budget Impact Analysis of Against Colorectal Cancer In Our Neighborhoods (ACCION): A Successful Community-Based Colorectal Cancer Screening Program for a Medically Underserved Minority Population

Abstract: The budget impact mainly derived from colonoscopy-related costs incurred for the high-risk group. The effectiveness of FIT to detect CRC was critically dependent on follow-up after positive FIT. Community cancer prevention programs need reliable estimates of the cost of CRC screening promotion and the added budget impact of screening with colonoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…A total of 40 studies 1421,2427,29,3133,3538,4042,45,46,48,50,52,5465 were conducted in the U.S., and 13 studies 22,23,28,30,34,39,43,44,47,49,51,53,66 were conducted in other high-income countries. 13 The U.S. studies were distributed in the following geographic regions: Northeast, 15,18,24,37,38,46,50,52,58,62,63 Southeast, 17,18,26,27,55,64,65 Midwest, 14,16,25,36,42,45,54 Southwest, 19,20,29,33,35,56,5961 and West. 21,29–32,40,41,48,57 There were non-U.S. studies from Japan 22 and Spain 23 for breast cancer; from Japan 28 and Canada 30 for cervical cancer; and from Netherlands, 34,39 France, 47,49,53 Hong Kong, 51 South Korea, 66 and Italy 43,44 for colorectal cancer.…”
Section: Evidence Synthesismentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 40 studies 1421,2427,29,3133,3538,4042,45,46,48,50,52,5465 were conducted in the U.S., and 13 studies 22,23,28,30,34,39,43,44,47,49,51,53,66 were conducted in other high-income countries. 13 The U.S. studies were distributed in the following geographic regions: Northeast, 15,18,24,37,38,46,50,52,58,62,63 Southeast, 17,18,26,27,55,64,65 Midwest, 14,16,25,36,42,45,54 Southwest, 19,20,29,33,35,56,5961 and West. 21,29–32,40,41,48,57 There were non-U.S. studies from Japan 22 and Spain 23 for breast cancer; from Japan 28 and Canada 30 for cervical cancer; and from Netherlands, 34,39 France, 47,49,53 Hong Kong, 51 South Korea, 66 and Italy 43,44 for colorectal cancer.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…1417,2022,24,25,29–32,3443,4550,5254,5658,62,64,66 Most included cost-effectiveness analyses, reporting ICERs, 1416,18,2024,26,27,2933,3538,40,41,45,47,49,57,60,62,6466 whereas some reported only cost estimates. 17,19,25,28,34,39,4244,46,48,5456,58,59,61 Only one study reported cost–benefit estimates. 63 Of the studies reporting cost-effectiveness estimates, the majority had comparators that did not receive an intervention (usual-care group).…”
Section: Evidence Synthesismentioning
confidence: 99%
See 3 more Smart Citations